Application of Next Generation Sequencing Genetic Studies of Urea Cycle Disorders - Huong, Nguyen Thi Thu; Kim Lien, Nguyen Thi; Hoang, Nguyen Huy (VNU Journal of Science: Natural Sciences and Technology, 2021)
Urea cycle disorder is a group of rare, inherited metabolic disorders in the pathway transforming ammonia to urea. The mutations in genes coding for 6 enzymes that are participated including carbamoyl phosphate synthase I (CPSI), ornithine transcarbamylase (OTC), argininosuccinate synthase (ASS1), argininosuccinate lyase (ASL), arginase (ARG1), and N-acetyl glutamate synthase (NAGS), and 2 transport systems ((ornithine translocase (ONT1), citrin)) in the urea cycle are responsible for ammonia accumulation in the blood. Hyperammonemia is the cause of severe neurological symptoms and even death. In almost all cases, clinical examinations and biochemical experiments are necessary, but insufficient information for an accurate diagnosis. Mutation analysis is an effective method to confirm the diagnosis and could be the basis for genetic counseling. The rapid development and widely using of next generation sequencing (NGS) have brought incredible advances in molecular diagnosis of genetic diseases in general. In this article, we systematize the UCD genetic studies applying NGS method, thereby providing a basis for not only disease diagnosis but also future research